Validation and clinical interpretability of PsAID - psoriatic arthritis impact of disease - Elziane da Cruz Ribeiro e Souza; Sueli Coelho da Silva Carneiro; Michel Alexandre Yazbek; Rita de Cássia Menin; Cristiano Barbosa Campanholo; Jamille Nascimento Carneiro; Carlos Henrique Martis da Silva; Roberto Ranza (Advances in Rheumatology, 2020)
Abstract Background Psoriatic arthritis (PsA) is a chronic inflammatory disease of widely varying presentation, which determines functional and psychological impairment, with a high negative impact on patients’ quality of life. Therefore, knowing the patient’s perception of their health status is of fundamental importance for understanding the real impact of PsA. Given this context, the European League Against Rheumatism (EULAR) recently developed the Psoriatic Arthritis Impact of Disease (PsAID) - instrument to specifically assess the impact of PsA for the patient. Objective Validate the brazilian portuguese version of PsAID-12 (Psoriatic Arthritis Impact of Disease) and to verify its interpretability in clinical practice, through its relation with measures of psoriatic arthritis activity. Methods A multicenter cross-sectional study, which recruited 160 patients, who met the Classification criteria for Psoriatic Arthritis (CASPAR), in six Brazilian centers of rheumatology. Reliability was assessed by Cronbach’s alpha coefficient and by the intraclass correlation coefficient (ICC). The construct validity was evaluated by exploratory factorial analysis and also by Spearman correlation with other PROMs and measures of disease activity evaluation. Results Of the total number of participants, 50% were female, with a mean age (SD) of 54.0 ± 11.2 years; 68% had only peripheral arthritis and 32% had pure or mixed axial involvement. The majority (67.7%) of the patients were using biological treatment. The reliability of internal consistency (alpha-Cronbach = 0.93) and test-retest (ICC = 0.996) were good. Factor analysis revealed two factors, named physical and psychosocial, which included the skin evaluation item. PsAID-12 correlated significantly with other PROMs, demonstrating good construct validity. PsAID-12 was also significantly associated with the disease activity assessment instruments (DAS28-ESR, ASDAS, and BASDAI) and the MDA status: “Minimum Disease Activity”. Fibromyalgia did not significantly affect the final PsAID-12 score. Conclusion The brazilian version of PsAID-12 has been shown to be a reliable and valid measure of the impact of the disease in patients with psoriatic arthritis. Moreover, it associated significantly with the scores of disease activity assessment.